Coleus barbatus Benth and Ocimum basilicum L. (Lamiaceae), New Host Plants to Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae) in Sinop, State of Mato Grosso, Brazil - Pires, Evaldo Martins; Manica, Clovis Luiz de Moraes; Nogueira, Roberta Martins; Carneiro, Jeandson da Silva; Rodrigues, William Costa; Soares, Marcus Alvarenga (EntomoBrasilis, 2014)
Coleus barbatus Benth and Ocimum basilicum L. are plants species commonly used for medicinal and gastronomic purposes, respectively. Caterpillars of the Spodoptera genus are generalists due to the wide variety of plants species used as food souce. The aim of this research was record the occurrence of Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae) in Sinop, Mato Grosso State, Brazil, and also record C. barbatus and O. basilicum as potencial host plants for this insect species. It is recommended attention in inclusion of S. cosmiodides in Integrated Pest Management (IPM) of this plant species. Coleus barbatus Benth e Ocimum basilicum L. (Lamiaceae): Novas Plantas Hospedeiras para Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae) em Sinop, Estado de Mato Grosso, Brasil Resumo. Coleus barbatus Benth e Ocimum basilicum L. são espécies de plantas comumente utilizadas com fins medicinais e gastronômicos, respectivamente. Lagartas do gênero Spodoptera são generalistas devido à ampla variedade de plantas que utilizam como recurso alimentar. O objetivo desta pesquisa foi registrar a ocorrência de Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae) no município de Sinop, Mato Grosso, Brasil, e ainda, relatar C. barbatus e O. basilicum como potenciais plantas hospedeiras para esta espécie de inseto. Recomenda-se ainda a inclusão de S. cosmioides em monitoramentos visando o Manejo Integrado de Pragas (MIP) nestas plantas.